Modelling of Separation and Air Classification Processes of Aerodisperse Systems in the Shelving Device - Varukha D. A.; Smirnov V. А.; Edl M.; Demianenko M. M.; Yukhymenko M. P.; Pavlenko I. V.; Liaposhchenko O. O. (Журнал інженерних наук)
The following paper considers the process of classification of polydisperse free-flowing material according to granulometric composition using a gravitational air classificator. There were considered the problems of the purity of separation of polydisperse bulk materials and methods for increasing the degree of separation of particles. There were presented and analyzed obtained the results of the comparison, the data of experimental research and computer simulation of two-phase hydrodynamics flow by CFD methods. The versatility of this complex allowed carrying out simulation of the process using various parameters. As a result, were obtained optimal operating parameters, which were experimentally verified. Based on the obtained data as a result of numerical modelling, the possibility of increasing gas flow influence to the polydispersed material were found, as well as organization along the walls of coarse fraction downward flow by dint of the optimizing the devise design (specifically through the organization of additional inlets for airflow) were obtained.